The Role of International Islamic Economic Institutions in Rationalizing Islamic Banks (Islamic Sciences Journal, 2023)
Praise be to Allah, Lord of the Worlds, and prayers and peace be upon His faithful Messenger and his family and companions until the Day of Judgment... and afterEconomy, trade, market, employment, growth and inflation ... are terms that have significance in the world of economy, closely related to banking, from organizing the movement of money and its transfer to managing cash liquidity and making profits, for banks to regulate the ways of commercial agreement between the contracting parties, with prior identification of the type of contracts and supervision of their implementation , in accordance with the direction of the bank, to appear types of banks that may be similar in many aspects of banking work, with difference in theories of achieving profit or development.Some of these banks depend on making profits through usurious transactions, and some of them are based on the adoption of development such as, Islamic banks based on the jurisprudence of financial transactions ,although they are new in their construction they are old in their thought and economic and jurisprudential performance, in terms of making money, agiotage, and participation. Islamic law is safer in terms of dealing, and more effective in terms of development, because it is far from relying on interest (usury) in the development of its assets; Here appears the role of Islamic economic institutions in directing Islamic banks to unite in terms of their orientation, and to organize their work in proportion to the economic changes, especially after the Corona pandemic, and the repercussions of the global market, which will have a negative impact on Muslim countries and the region in general.
Keywords: Sharia bodies, economics, banks, risk management, development, jurisprudence of transactions .